Mission statement and social impact: Shedding light on the contribution of Italian B corps to society - Mion, Giorgio; Bonfanti, Angelo; De Crescenzo, Veronica; Loza Adaui, Cristian R. (Long Range Planning, 2024)
This qualitative study examines the relationship between the mission statements of 161 Italian B Corps and their social impact performance, measured by the B Impact Assessment (BIA). The research combined different qualitative methods: content analysis, text mining, and fuzzy-set qualitative comparative analysis (fsQCA) in a homogeneous research design to explore the content of B Corps mission statements and their influence on social impact performance. The results reveal that B Corps’ mission statements are compound in nature, combining elements related to philosophy and values, environmental protection, and social benefit with the drive toward market success and economic performance. Additionally, mission statements with rich content are associated with better social impact performance, highlighting the role of the mission statement in creating identity and imprinting differentiation for B Corps. Finally, this study offers practical recommendations for entrepreneurs and managers of B Corps to craft clear mission statements that promote positive social impact.<br
Keywords: Mission statementsSocial impactB corpsSocial entrepreneurshipSocial-oriented businessesManagerial ambidexterityBenefit impact assessmentContent analysisText miningfsQCA